CARTA DE LOS DIRECTORES - Daniel García San José, Fernando LLano Alonso (IUS ET SCIENTIA, 2016)
En este número continuamos publicando las ponencias del Congreso Internacional "Ciencia Biomédica y Derechos Fundamentales", celebrado en la Universidad de Sevilla el 1 y 2 de Diciembre de 2016. In this issue we continue publishing the articles produced in the International Congress: "Biomedical Science and Fundamental Rights", held in the University of Seville (Spain) on 1st and 2nd December 2016.